(3cJGH GdMebi hGdeZadjfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3eMeO Hf eMeO Hf eMeO Hf eMeO GdYQGbi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYWi ef GdEfYGe LRjdkG hbHd ef GdTcQ bdjdkG TQYJ ai CNHGQ GdGPcjG hPcQJ HYV Gdfbhd s
(3BNQgG (B:s
(3abGd HYV GdeZadjf bO eGJ ai gPg GdSfI ef de jeJ bW fLR GdcJGH GdeHGQc HMeO Gddg JYGdi hYhfg s
(3GdfSNI HgG MhGTs
(3HChQGbgG GdChdi CKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs